2014
DOI: 10.3171/2014.3.focus13368
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and clinical outcomes following combined lateral lumbar interbody fusion and posterior segmental stabilization in patients with adult degenerative scoliosis

Abstract: Object A hybrid approach of minimally invasive lateral lumbar interbody fusion (LLIF) followed by supplementary open posterior segmental instrumented fusion (PSIF) has shown promising early results in the treatment of adult degenerative scoliosis. Studies assessing the impact of this combined approach on correction of segmental and regional coronal angulation, sagittal realignment, maximum Cobb angle, restoration of lumbar lordosis, and clinical outcomes are needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 54 publications
5
36
1
1
Order By: Relevance
“…The few studies using open fixation did not specify the frequency or number of facet osteotomies. 4,23,28,30 The LIF+OP approach also provided more LL restoration than our OP-only operations without PSO (11° ± 7°). Most of our patients were in their 7th or 8th decades with stiff, collapsed discs.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The few studies using open fixation did not specify the frequency or number of facet osteotomies. 4,23,28,30 The LIF+OP approach also provided more LL restoration than our OP-only operations without PSO (11° ± 7°). Most of our patients were in their 7th or 8th decades with stiff, collapsed discs.…”
Section: Discussionmentioning
confidence: 76%
“…23 Other studies have reported modest improvements in LL (5°-8°) and SVA (0-2.5 cm), with coronal correction more substantial. 4,7,24,28 Consequently, LIF has been recommended for only small sagittal correction goals (10° in LL and 5 cm in SVA). 10 A key shortcoming of these studies was limited use of traditional open posterior techniques for deformity correction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although most studies of LLIF have reported favorable radiographic results after the correction of coronal deformity, the amount of sagittal plane correction was relatively suboptimal, with a 1.6–9.0° increase in LL [91112131415161718]. We postulated that these suboptimal results are attributable to the fact that the L5–S1 levels were not operated or were operated using the posterior fusion technique.…”
Section: Introductionmentioning
confidence: 99%